PENYULUHAN DAN PELATIHAN INTERNET SEHAT UNTUK ANAK USIA SEKOLAH MENENGAH PERTAMA (SMP) PADA KELURAHAN CIPARE KECAMATAN SERANG KOTA SERANG - Ely Nuryani; Yul Hendra; Irma Yunita Ruhiawati (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Internet is something that can be easily accessed by everyone. With just one click it can take people anywhere even to a different world. Inaccurate use of the internet can carry considerable negatives. For adolescents who are still in their teens who still have a passion for learning and high curiosity can take advantage of the internet. However, not a few teenagers who actually use the internet get a negative impact because of their lack of knowledge of the internet; they do not understand the negative effects that can be caused by the internet. This is due to the lack of explanation and education related to the internet to them. Therefore, how important the role of parents, teachers, and society is in providing explanation, understanding, and education to adolescents related to the internet. One of the solutions that can solve the above problems is the holding of Healthy Internet Counseling and Training for Junior High School-aged Children (SMP) with the aim of providing understanding to junior high school age children regarding healthy use of the internet and to find out what the negative impacts of the internet are. Community service activities in the form of counseling and training for healthy internet get results and benefits including increasing sufficient understanding of the wise use of the internet so as to maximize the positive impact of the internet and minimize the negative impact of surfing, so as to create smart and productive teenagers.